Ramazzottius bunikowskae, a new species of Tardigrada (Eutardigrada, Hypsibiidae) from Russia - Kaczmarek, Łukasz; Michalczyk, Łukasz; Diduszko, Dawid (Zootaxa, 2006)
A new species, Ramazzottius bunikowskae sp. nov. is described from a lichen sample collected in Russia. The new species is the most similar to R. caucasicus Biserov, and R. tribulosus Bertolani & Rebecchi in the shape of the egg processes but it differs from these species by some differences in the egg processes’ appearance and measurements and also by measurements of some structures in adult specimens. We also provide first observations of peribuccal lobes, papillae and porous areas on the head (possibly external parts of chemoreceptors) in the genus Ramazzottius.